2017
DOI: 10.1159/000477098
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Swept-Source Optical Coherence Tomography of Early Enamel Erosion in vivo

Abstract: Swept-source optical coherence tomography (SS-OCT) shows potential for the in vivo quantitative evaluation of micro-structural enamel surface phenomena occurring during early erosive demineralization. This randomized controlled single-blind cross-over clinical study aimed to evaluate the use of SS-OCT for detecting optical changes in the enamel of 30 healthy volunteers subjected to orange juice rinsing (erosive challenge) in comparison to mineral water rinsing (control), according to wiped and non-wiped enamel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Austin et al . proposed an analysis method for evaluating the influence on the OCT backscattered intensity of enamel surface due to orange juice rinsing 29 . Habib et al .…”
Section: Introductionmentioning
confidence: 99%
“…Austin et al . proposed an analysis method for evaluating the influence on the OCT backscattered intensity of enamel surface due to orange juice rinsing 29 . Habib et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, this approach uses a polishing step which removes the outer mineral rich layer. To determine the presence and subsequent progression of these natural surface erosion lesions, changes in surface form, surface roughness, and surface optical properties have been studied previously [18,[21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The number of several OCT studies already demonstrated in dentistry that OCT can be used to nondestructively measure the severity of the lesion in enamel with cross-polarization optical coherence tomography (CP-OCT), swept-source optical coherence tomography (SS-OCT) images 6,[11][12][13] . The principal purpose of this study was to demonstrate the efficacy of different remineralization agents on artificial lesions using the high-definition (HD) spectral-domain optical coherence tomography (SD-OCT) and to compare it with the surface microhardness (SMH) analysis.…”
Section: Introductionmentioning
confidence: 99%